Comparison of Multidimensional and Unidimensional Approach to Entrepreneurial Orientation: A Systematic Literature Review for SDG 8 - Rusnandari Retno Cahyani; Asri Laksmi Riani; Mugi Harsono; Sinto Sunaryo (Journal of Current Studies in SDGs, 2027)
Objective: To examine and compare the multidimensional and unidimensional approaches to Entrepreneurial Orientation (EO) and their contribution to organizational performance within the perspective of sustainable economic development aligned with Sustainable Development Goal (SDG) 8. EO represents a strategic capability that encourages innovation, competitiveness, and entrepreneurial activities in organizations. Method: A Systematic Literature Review (SLR) approach by analyzing peer-reviewed articles indexed in Scopus from 2014 to 2024. From 500 initially identified articles, 100 articles were selected through screening, full-text evaluation, and quality assessment processes. The analysis focused on EO dimensions, research trends, theoretical contributions, and comparative advantages of both approaches. Results: The findings indicate that the multidimensional approach provides deeper insights into the specific roles of innovation, proactiveness, risk-taking, autonomy, and competitive aggressiveness in influencing organizational outcomes. Meanwhile, the unidimensional approach offers a simpler and more practical measurement framework for assessing overall entrepreneurial orientation. Both approaches demonstrate significant contributions to understanding business performance and entrepreneurial success. Novelty: The study contributes by integrating multidimensional and unidimensional perspectives of EO into a comprehensive framework that supports sustainable entrepreneurship development. The findings provide theoretical and practical implications for organizations seeking innovation-driven growth and sustainable economic competitiveness aligned with SDG 8.